The Impact of Role Models on Youths' Aspirations, Gender Attitudes and Education in Somalia - Elijah Kipchumba; Catherine Porter; Danila Serra; Munshi Sulaiman (Institute of Labor Economics (IZA), 2024)
We evaluate the impact of a role model intervention on the gender attitudes, college aspirations and education outcomes of youths in Somalia. In 2018, we randomly selected elementary schools to receive a visit from a college student. Within each treatment school, we selected four grades, two to receive a visit from a female college student and two from a male college student. The "role models" gave unscripted talks about their personal study journeys, including challenges and strategies to overcome setbacks. Six months after the intervention we found a significant and large impact of (only) female role models on boys' and girls' attitudes toward gender equality but no impact on college aspirations. Data collected two and four years later from the cohorts graduating primary school produce smaller and non-significant treatment effects on the survey outcomes, but positive impacts on enrollment in high school and a lower probability of early marriage as reported by teachers.
Keywords: J16; O12; I25; C93; 330; role models; education; gender; aspirations; field experiment; Somalia